Thermographic analysis of bronze sculptures. (3rd July 2016) - Orazi, Noemi; Mercuri, Fulvio; Zammit, Ugo; Paoloni, Stefano; Marinelli, Massimo; Giuffredi, Augusto; Salerno, Carlo Stefano
Abstract : In this work we investigate various aspects of the finishing process in ancient bronze sculptures by means of active infrared thermography (IRT). Active IRT provides information on surface and sub-surface features of the investigated artefact, by analysing the heat diffusion process induced within the sample by appropriate thermal stimulations usually produced by absorption of light emitted by different sources. The aim of this research is, in particular, to investigate the processing of bronze surfaces, revealing repairs like plugs, fillings, local castings and concealed marks.